Contribuição para o conhecimento geológico e geomorfológico da praia de Lavadores (Vila Nova de Gaia) - Ferreira, Jorge (2014)
Lavadores' beach stands on the South of the Douro's river mouth about 2 km from Porto. It's the only sector of litoral "high" coast at the South of Douro's. This beach stays very close to the passage through the coastline of the Porto-Tomar fault, which corresponds to the contact between the Central-Iberian and Ossa-Morena zones. Posttectonics granite’s are outcropping in this beach. The fracture net seems to control the development of the coastline, imposing a rigid orientation to the cliffs as well on certain rectlineous corridors inside between the granites’ walls, which are usually abrupt. The same fracture net controls the existence of a typical block disjunction and other geomorphologic aspects of detail. We pretend to present geological and geomorphological sketches of the exposed rocks at the Lavadores beach and discuss the relationship between the geological structure (fracture net, neotectonics) and the forms due to the marine erosion.